2009
DOI: 10.1007/s00227-009-1138-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects on multi-element composition of European eel (Anguilla anguilla) otoliths

Abstract: Otolith microchemistry is widely used as a tool to track individual migration pathways of diadromous Wsh under the assumption that the elemental composition of Wsh otoliths is directly inXuenced by the physicochemical properties of the surrounding water. Nevertheless, several endogenous factors are reported to aVect element incorporation into Wsh otoliths and might lead to misinterpretations of migration studies. This study experimentally examined the inXuence of eight diVerent diets on the microchemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…However, as we show here, many migrant fish species presented similar ranges of Ba:Ca ratios in their otoliths along the Patos Lagoon estuary. Also, most studies indicate that water is the major source of otolith elements and that diet has little or no effect on otolith elemental composition (Walther & Thorrold 2006, Gibson-Reinemer et al 2009, Marohn et al 2009), which helps to discard potential confounding effects of diet in our results. In contrast to Ba:Ca, individual Sr:Ca profiles exhibited low variation, with an overall tendency to increase with age, re gardless of which site individuals were collected from ( Fig.…”
Section: Resultsmentioning
confidence: 87%
“…However, as we show here, many migrant fish species presented similar ranges of Ba:Ca ratios in their otoliths along the Patos Lagoon estuary. Also, most studies indicate that water is the major source of otolith elements and that diet has little or no effect on otolith elemental composition (Walther & Thorrold 2006, Gibson-Reinemer et al 2009, Marohn et al 2009), which helps to discard potential confounding effects of diet in our results. In contrast to Ba:Ca, individual Sr:Ca profiles exhibited low variation, with an overall tendency to increase with age, re gardless of which site individuals were collected from ( Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Alternatively, the influence of diet in the Sr and Ba incorporation is also widely discussed (Buckel et al 2004;Marhon et al 2009). Lefrançois et al (2011) showed that a mean of 25 to 31% of S. punctatum diet is provided by the epilithic biofilm growing on wet stones on the river bed in Caribbean rivers.…”
Section: Changes In Barium Biogeochemistry At the Habitat Scalementioning
confidence: 99%
“…Furthermore, studies that have examined the effect of diet on Sr and Ba otolith chemistry, either through artificial enrichment of food or changing natural food types, suggest that diet has either no effect (Hoff & Fuiman 1995, Milton & Chenery 2001, Marohn et al 2009), or a significant and/or detectable effect on otolith chemistry (Limburg 1995, Gallahar & Kingsford 1996, Buckel et al 2004, Engstedt et al 2012. In regards to the latter group, however, it is difficult to assess to what level diet influences otolith chemistry relative to water, particularly if diet effect has only been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also examined the influence of diet on Sr otolith chemistry in freshwater species through diet manipulation (e.g. changing food type or enriching food with specific elements); however, they report conflicting results (Limburg 1995, Milton & Chenery 2001, Marohn et al 2009), which was also observed in analogous studies on marine and estuarine species (see Hoff & Fuiman 1995, versus Buckel et al 2004.…”
Section: Abstract: Otolith Chemistry · Freshwater Fish · Water · Diementioning
confidence: 99%